Hambatan Dan Strategi Coping Mahasiswa Calon Guru Bahasa Inggris Selama Pengenalan Lapangan Persekolahan (PLP): Studi Kualitatif Deskriptif - Tri Winindyasari Palupi; Fathul Zannah; Desi Hidayanti (Bajang Institute, 2026)
Abstrak: The School Field Introduction Program (Pengenalan Lapangan Persekolahan/PLP) is an essential component of teacher education that develops pre-service teachers' competencies through authentic teaching experiences; however, many students encounter challenges during its implementation. This study aimed to identify the challenges experienced by English Language Education students during PLP and to describe the coping strategies they employed to overcome them. Using a descriptive qualitative approach, data were collected from five sixth-semester students of the English Education Study Program at Universitas PGRI Kalimantan through semi-structured interviews and lesson plan document analysis, then analyzed through data condensation, data display, and conclusion drawing (Miles, Huberman, & Saldaña, 2020). The findings revealed three major challenges: lack of self-confidence in classroom teaching, difficulties in preparing and adapting lesson plans to actual classroom conditions, and limited guidance from mentor teachers. To address these challenges, participants employed problem-focused strategies, including thorough preparation, utilizing instructional media, and adapting instruction to classroom situations, as well as emotion-focused strategies, including building mental readiness, ice-breaking activities, and peer discussions. The findings confirm the role of PLP in strengthening pre-service teachers' professional competence, independence, and adaptability, and highlight the need to improve preparation and mentoring systems in teacher education